(untitled) (Research, Society and Development, 2020)
In Brazil, Professional and Technological Education (EFA) has historically been characterized by duality, in which intellectual education is directed to economic elites and technical education to the vast majority of the population, notably the least economically favored people. The EPT federal network, in an emancipatory perspective, currently proposes the rupture of this dual system based on the valuation and interdependence of propaedeutic knowledge with the technical knowledge of production processes. However, overcoming this educational paradigm is related to the understanding of teacher education and pedagogical practice. In this sense, this article, based on the research proposal presented by Maria Isabel da Cunha (1989), aimed to investigate who is the “Good Teacher” of Professional and Technological Education and its practice from the point of view of undergraduate students of the IFNMG Campus Montes Claros. Thus, in the first semester of 2019, 8 (eight) students from the 3rd period of the Electrical Engineering course were interviewed and 16 (sixteen) students from the 7th period of the Chemical Engineering course. The results were analyzed using the Collective Subject Discourse (CSD) methodology. According to the respondents’ DSC, the “Good Teacher” is the one who presents an innovative, critical and creative practice, which has an interpersonal relationship with students based on respect, trust, patience and knowledge exchange. It was noticed that there were similarities in the results presented in the studies of Cunha (1989), however, there was evidence of the use of innovative practices, reaffirming the idea that the education process is constantly changing and adapting.